The European dimension in education in geography textbooks for Croatian primary schools : lessons learned and future expectations - Vignjević Korotaj, Bojana (Array, 2020)
Croatia's accession to the EU brought changes in educational policies by introducing the concept of the European Dimension in Education (EDE). EDE has successfully found its way into the new Croatian national curriculum, however, there has been no comprehensive analysis of whether it has been introduced into teaching materials (textbooks). Therefore, the aim of this paper is to determine if the European Dimension in Education is present in geography textbooks for primary schools, as well as to explore how it is represented in them. The results of research show that the idea of the European Dimension in Education is most commonly present in terms of factual knowledge about Europe, which does not motivate teachers and pupils to actively and critically discuss issues related to Europe and the European Union.